Hydrogen Aircraft, Technologies and Operations Towards Certification Readiness Level 1 - Gregory O’Sullivan; Andrej Bernard Horvat; Joël Jézégou; Beatriz Jiménez Carrasco; Robert André (Aerospace, 2025)
Aviation has become an essential part of the modern world’s ability to grow personal, market and international connections. To enable continued benefits while reducing emissions, future aircraft will need radical redesign and novel, complementary technologies. Hydrogen aircraft are potentially the means to emissions reduction. As part of the European Union’s (EU’s) Clean Aviation Joint Undertaking (CAJU), it is aimed to have hydrogen aircraft entering into service by 2035. To realise this, it would require the certification of these aircraft in a relatively short timeline, which the CONCERTO project aims to help enable. Given the lack of mature experimental designs and pending certification processes, this endeavour is ambitious. To accelerate this, dedicated preparation for the certification through regulatory analysis should be complete, requiring initial options for technologies and aircraft operations to be defined. The technologies and operations were defined, analysed and weighted in CONCERTO, upon which a Generic Concept was made, outlined in this paper, with Level 1 on the Certification Readiness Level Scale. The aircraft systems which are likely to experience the largest changes; Fuel Storage, Fuel Distribution, Propulsion, Auxiliary Power Unit (APU), Heat Exchange (HEX) System and Sensing and Monitoring for Hydrogen (H2), will be outlined in this paper with respect to their components and integration challenges, and the subsequent changes to operations to enable this.